1993
DOI: 10.1101/gad.7.5.895
|View full text |Cite
|
Sign up to set email alerts
|

Multiple extracellular signals govern the production of a morphogenetic protein involved in aerial mycelium formation by Streptomyces coelicolor.

Abstract: The formation of an aerial mycelium by the filamentous bacterium Streptomyces coelicolor is determined in part by a small morphogenetic protein called SapB. A collection of representative bald (bld) mutants, which are blocked in aerial mycelium formation, are all defective in the production of this protein and regain the capacity to undergo morphological differentiation when SapB is supplied exogenously. We now report that most of the bid mutants are rescued for SapB production and aerial mycelium formation wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
209
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(216 citation statements)
references
References 22 publications
5
209
0
2
Order By: Relevance
“…The bldJ mutant is particularly interesting because it is predicted to be impaired in the production of the very first signal of the cascade that leads to the onset of S. coelicolor morphological differentiation. [38][39][40] The reduced siderophore production in bldJ mutants is unlikely to be the consequence of impaired expression of siderophore biosynthetic genes as desA, cchB and even SCO5800 for the cryptic siderophore were transcribed at similar levels as in the wild-type strain M145 (Fig. 7).…”
Section: Down-regulation Of Siderophore Uptake Systems In the Bldj Mumentioning
confidence: 99%
See 1 more Smart Citation
“…The bldJ mutant is particularly interesting because it is predicted to be impaired in the production of the very first signal of the cascade that leads to the onset of S. coelicolor morphological differentiation. [38][39][40] The reduced siderophore production in bldJ mutants is unlikely to be the consequence of impaired expression of siderophore biosynthetic genes as desA, cchB and even SCO5800 for the cryptic siderophore were transcribed at similar levels as in the wild-type strain M145 (Fig. 7).…”
Section: Down-regulation Of Siderophore Uptake Systems In the Bldj Mumentioning
confidence: 99%
“…[38][39][40] In the proposed model for the developmental signalling cascade it has been shown that S. coelicolor produces and exports the very first signal of morphogenesis through the product of genes associated with the bldJ mutation. After extracellular accumulation of this signal, it is imported through the BldK oligopeptide permease, triggering the next step in the cascade.…”
Section: Down-regulation Of Siderophore Uptake Systems In the Bldj Mumentioning
confidence: 99%
“…Spores or mechanically macerated mycelia were spread on porous cellophane-covered minimal medium with mannitol (Willey et al, 1993). Mycelia were harvested at various times by scraping off the cellophane and resuspending in 1.5 l of lysis buffer per mg wet weight.…”
Section: Western Blot Protocolmentioning
confidence: 99%
“…We studied two S. coelicolor bld mutants [bldA (J1700) (Merrick, 1976;Lawlor et al, 1987), bldC (J660) (Merrick, 1976)] and three whi mutants [whiB (Chater, 1972), whiJ (C77) (Chater, 1989) and whiG (C71) (Chater, 1972)] and their parental strains lacking these mutations ( activity increased in the parental S. coelicolor strains, the three whi mutants studied, and a bldC mutant as these various bacteria progressed through their life cycle in solid media (shown only for whiG, Fig. 7, lanes 5-7), as had been observed for S. lividans strain TK64, the bldA mutant, which blocks both morphological and physiological development (Merrick, 1976;Lawlor et al, 1987) at an earlier stage than bldC (Willey et al, 1993), showed no increase in RNase ES activity during growth (Fig. 7, lanes 8-10).…”
Section: Resultsmentioning
confidence: 68%
“…However, a bldA mutant, which is thought to be blocked at an earlier stage in development (Willey et al, 1993) and fails to show any antibiotic production or aerial mycelia formation (Merrick, 1976;Lawlor et al, 1987), did not show increased RNase ES activity during the S. coelicolor life cycle. Thus, the events that lead to increased RNase ES activity during development appear to occur subsequent to the action of bldA, but before that of bldC.…”
Section: Discussionmentioning
confidence: 95%